PENGARUH BRAND COMMUNITY TRUST, BRAND COMMUNITY AFFECT, BRAND COMMUNITY CHARACTERISTICS TERHADAP BRAND LOYALTY MELALUI BRAND COMMUNITY COMMITMENT - Dian Annisa; Agus Suroso; Sri Martini (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2013)
This study is a survey research on member in online community id-blackberry. The purpose of this study was to examine the influence of Brand Community Trust, Brand Community Affect, Quality of Information. Quality of System, Interactivity, Reward For Activities, Brand Community Commitment, Repurchase Intention, Word of Mouth, Constructive Complain. According to research’s result and data analysis which using Strucutral Equation Modelling (SEM) as tool analysis and AMOS 18.0 as software, shown that (1) brand community trust have significant effect to brand community commitment; (2) brand community affect have significant effect to brand community commitment; (3) quality of information have significant effect to brand community commitment, (4) quality of system have significant effect to brand community commitment, (5) interactivity have significant effect to brand community commitment, (6) reward for activities have significant effect to brand community commitment, (7) brand community commitment have significant effect to repurchase intention, (8) brand community commitment have significant effect to word of mouth, (9) brand community commitment have significant effect to constructive complain.